A new species of Trichuris Roederer, 1761 (Nematoda: Trichuridae) from Heteromys gaumeri Allen & Chapman (Rodentia: Heteromyidae) in Yucatan, Mexico - Panti May, Jesus Alonso (2016)
In Mexico, four species of Trichuris Roederer, 1761 have been recorded in wild rodents belonging to the family Heteromyidae. In the present paper, we describe a new species based on specimens collected from Heteromys gaumeri Allen & Chapman (Heteromyidae: Heteromyinae) in the tropical forests of the Yucatan Peninsula, Mexico. Trichuris silviae n. sp. can be differentiated from the congeners described in North and South American rodents by morphological and morphometric features, such as the possession of a wide spicular tube, a thicker proximal cloacal tube, a shorter distal cloacal tube and a cylindrical spicular sheath. This is the first description of a Trichuris spp. from heteromyid rodents in Mexico and the fourth in North America. Despite the broad distribution of Heteromys spp., few cases of Trichuris infection have been reported. Further studies are necessary to verify if the new species is present in other heteromyid rodents in order to increase our knowledge about its geographical and host distribution.